Attosecond SXR spectroscopy reveals many-body dynamics in solids - Sidiropoulos, T.P.H.; Tyulnev, I.; Di Palo, N.; Rivas, D. E.; Summers, A.; Severino, S.; Reduzzi, M.; Biegert, J. (SPIE, 2024)
We employ attosecond core-level x-ray absorption spectroscopy to unravel the intricate many-body interactions occurring in strongly photo-excited semi-metallic graphite. This allows us to unveil remarkably high conductivity and delineate deviations from the single particle bandstructure.